Digital Readiness and Action Prioritization in Small Cosmetics Manufacturers - Tariq Hasan Fadhil; Jurry Hatammimi (Transpublika Publisher, 2026)
Small cosmetics manufacturers frequently adopt digital applications before their internal routines, data controls, and workforce capabilities are ready to support them. This condition creates operational fragmentation rather than integrated transformation. This study assesses digital readiness, identifies the factors that support and constrain transformation, and develops a staged set of managerial priorities for a resource-limited cosmetics manufacturer in Indonesia. An explanatory sequential mixed-method design was used. The first stage applied the Indonesia Industry 4.0 Readiness Index survey to 33 respondents across five readiness dimensions, while the second stage used a cross-functional focus group discussion involving seven participants to interpret the survey results. The company obtained an overall readiness score of 1.21, which indicates initial readiness. People and culture had the strongest score at 1.87, whereas management and organization had the weakest score at 0.21. The evidence shows that employee willingness, management awareness, and an existing internal application provide a starting point, but progress is limited by the absence of a roadmap, formal team, dedicated budget, systematic training, and dependable real-time data. The study implies that early digital transformation should prioritize disciplined data entry, clear process ownership, and capability development before large technology investment.